Exploring adherence in patients with advanced breast cancer: focus on CDK4/6 inhibitors - Baković Matea; Bago Martina; Benić Lucija; Krajinović Magdalena; Silovski Tajana; Plavetić Natalija Dedić; Turković Lu; Sertić Miranda; Hadžiabdić Maja Ortner (Acta Pharmaceutica)
Treatment adherence is crucial for optimal outcomes in advanced breast cancer, but can be challenging due to various factors, i.e. patients’ attitudes and behavior upon diagnosis, and complex therapies with high adverse effect rates. Our aim was to explore the adherence to oral anticancer medications (OAM) in women with advanced breast cancer, focusing on cyclin-dependent kinase 4 and 6 inhibitors (CDKI), and identify factors associated with the adherence. We conducted a cross-sectional study at the University Hospital Centre Zagreb, Croatia, involving women with stage IV advanced breast cancer receiving OAM. Data collection included a questionnaire assessing socio-demographic and clinical information, Beck Depression Inventory-II for depressive symptoms, Medication Adherence Report Scale (MARS-5) for adherence to OAM, and Beliefs about Medicines Questionnaire. Plasma concentrations of CDKI were confirmed by LC-MS/MS in three randomly selected participants. A total of 89 women were included. The most prescribed OAMs were anti-estrogen (71.3 %) and CDKI (60.9 %). MARS-5 scores (mean: 24.1 ± 1.6) correlated with CDKI plasma concentrations. Forgetfulness was the primary reason for non-adherence (25.9 %). Women receiving CDKI (p = 0.018), without depressive symptomatology (p = 0.043), and with more positive beliefs about medicines were more adherent (p < 0.05). This study enhances understanding of medication adherence in advanced breast cancer and identifies influential factors.